Cara Membentuk Karakter Siswa Yang Baik Dan Intelektual Dan Luhur Kepada Budaya Indonesia Di Sekolah Dasar Cinta Kepada Warisan Budaya Dan Lingkungan Sebagai Implementasi Karakter Bela Negara Dan Rasa Cinta Tanah Air - Syafrina Nabila; Elfia Sukma (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Character building from an early age serves as the primary foundation in preserving the nation's noble values. This study aims to analyze and describe character building strategies for elementary school students oriented towards intellectual values, noble character based on Indonesian culture, and care for cultural heritage and the environment. This approach is integrated as a tangible manifestation of implementing national defense character and fostering a sense of patriotism within the school environment. The research method used is descriptive qualitative, with data collection through literature studies, participatory observation, and in-depth interviews. The results indicate that effective character building in elementary schools is successfully achieved through three main strategies: integrating cultural and environmental values into the learning curriculum (intracurricular), habituating local culture in daily school activities (cocurricular), and taking real action in environmental preservation and local wisdom (extracurricular). The implementation of this program is proven to enhance students' intellectual intelligence in balance with their emotional and spiritual intelligence. In conclusion, the synergy between Nusantara culture-based education and environmental preservation in elementary schools effectively fosters a robust spirit of national defense and a profound sense of patriotism among the younger generation.